Whole-Genome Analysis of Cryptococcus gattii, Southeastern United States - Shawn R. Lockhart; Chandler C. Roe; David M. Engelthaler (Emerging Infectious Diseases, 2016)
Cryptococcus gattii is a recognized pathogenic fungus along the Pacific coast of the United States from California to Washington. Here we report that C. gattii may also be endemic to the southeastern United States and has probably been present there longer than in the Pacific Northwest.